PEMANFAATAN INTERNET UNTUK BELAJAR PADA MAHASISWA - Birrul Walidaini; Ali Murtadha Muhammad Arifin (Jurnal Penelitian Bimbingan dan Konseling, 2018)
Internet has a variety of information resources and has many benefits for the wearer, especially students. In fact is the student is less appropriate in utilizing the internet to learn. The purpose of this research is to describe student’s internet use. Research used quantitative with descriptive  method. Population of research is 625 and 244 samples of guidance and counseling majors students, Universitas Negeri Padang. Instruments of this research used  Likert scale model, value of reliability are 0.841 and 0.842. Data were Analyzed with simple regression. Result of research shows that student’s internet use is category exact. Keywords: Internet Use, Student